Pengaruh metode pembelajaran pada masa pembelajaran tatap muka terbatas terhadap minat dan motivasi belajar matematika siswa SMK - Anggi Maulana; Hepsi Nindiasari; Syamsuri Syamsuri (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this study was to obtain a structural equation model related to learning method variables on students' interest and motivation to learn, to find out the effect of learning methods on students' interest and motivation to learn, and to know the correlation between students' interest and motivation to learn. this research method is quantitative with ex post facto approach. The results showed that the structural equation model obtained showed that the learning method could explain the interest in learning by 26% and the motivation to learn by 35%, the direct influence of the learning method on the student's interest in learning by 51.2%, the direct influence of the learning method on the student's learning motivation. by 59.7%, and there is a positive correlation between student interest and motivation of 76%. Thus, for further research, it is expected to investigate and reveal other factors outside of learning methods that contribute greatly to interest and motivation in learning mathematics student